Um corpo outro: Nuno Ramos, entre a literatura e as artes visuais - Julia Carolina Arantes (2017)
The purpose of this thesis is to investigate how the connection between body and language is manifested in Nuno Ramos literary and plastic works. Firstly, we will delve into a certain idea of body(the touching body) that appears in a number of selected literary texts from Nuno Ramos work. In this analysis, we aim to shift from the idea of matter as absolute immanence and incorruptible primordial power to a thought of the body as an exposed and deferred existence. Secondly, we will observe how the connection between literature and visual arts is developed. The starting point will be three formal and thematic approaches that provide the contact between arts in Nuno Ramos work: the composition method of juxtaposing contrasting elements; death as a theme and the subjectile as a presence in installations and literary texts. We will observe how these aspects are materialized in literature and in visual arts. Therefore, we will investigate how the artist works with the same technique or explores the same theme in different contexts. At last, pursuing a cyclical movement, we will return to those texts that explorethe idea of body in order to investigate how the contact between body and language manifests itself. We will analyze how both these notions approach one another, put strain onthe other and overflow into eachother. This contact between body and language produces, after all, sense. Philosophical theories such as différance, from Jacques Derrida, and the touching bodies, from Jean-Luc Nancy, are crucial for this present study, both working as a dynamo that reflects and reverberates the heterogeneous work of Nuno Ramos.